Efficacy and safety of electroacupuncture-based comprehensive treatment for post-stroke depression: a systematic review and meta-analysis of randomized controlled trials - Hu, Xiaomei; Pan, Yanying; Tang, Yasi; Zhang, You; Liu, Zhaoping; Zhuo, Yue; Zhang, Hong; Yi, Xiqin (Frontiers in Psychiatry, 2025)
ObjectiveThis research aims to assess the therapeutic effects and safety of treatments for PSD by conducting a thorough systematic review and meta-analysis.MethodsRandomized controlled trials (RCTs) were retrieved from PubMed, Embase, Web of Science, The Cochrane Library, China National Knowledge Infrastructure (CNKI), and Wan Fang, covering all available records up to September 30, 2024. RCTs evaluating on the efficacy and safety of electroacupuncture in individuals with PSD were included. The robustness of the findings and possible contributors to heterogeneity were examined via sensitivity and subgroup analyses. Statistical analyses were conducted utilizing STATA 15.0 and Review Manager 5.4.ResultsThis study included 65 RCTs with a total of 5,362 participants. The results showed that electroacupuncture exhibited significantly greater clinical effectiveness compared to the control group (RR = 1.16, 95% CI [1.11, 1.22], I² = 59%, p < 0.00001), effectively reducing HAMD scores (SMD = -0.56, 95% CI [-0.72, -0.40], I² = 87%, p < 0.00001), SDS scores (SMD = -0.56, 95% CI [-0.87, -0.24], I² = 90%, p = 0.006), and TCM-DS scores (SMD = -0.52, 95% CI [-0.78, -0.27], I² = 0%, p < 0.0001). The incidence of adverse reactions was lower in the electroacupuncture (EA) intervention group (RR = 0.54, 95% CI [0.35, 0.83], I² = 0%, p = 0.004).The most commonly used acupoints were primarily located along the Gallbladder, Bladder, and Du Meridian, with the five most frequently used acupoints being: Baihui (GV20, 41 times), Shenting (DU24, 28 times), Taichong (LV3, 28 times), Shenmen (HT7, 26 times), and Neiguan (PC6, 22 times).ConclusionElectroacupuncture could serve as a safe and effective complementary therapy for PSD. It is recommended that multicenter, large-scale, and high-quality RCTs be conducted to further validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024618618, identifier CRD42024618618